KONSEP DIRI PADA DEWASA AWAL YANG PERNAH MENJADI KORBAN PEDOFILIA DI KOTA MEDAN, SUMATERA UTARA - Anastasya, Gracia; Susilarini, Tanti (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
The purpose of this study was to determine self-concept in early adulthood who had beenvictims of pedophilia, in the city of Medan, North Sumatra. The form of pedophiliaexperienced can be known. The method used in this research is a qualitative researchmethod with a phenomenological approach and collects data through observation,psychological tests, interviews. The criteria for the subjects in this study were early adultsaged 20-30 years, individuals in this study were early adults who had experiencedpedophilia during childhood. The first subject was 30 years old and experiencedpedophilia during grade 1sd. The second subject was 27 years old and experiencedpedophilia when he was 5 years old. The third subject aged 20 years experiencedpedophilia during grade 6 sd. In this study, it will be seen how the self-concept ofsubjects who have been victims of pedophilia in early adulthood. The results showed thatin subject I and III, although the subject experienced unpleasant things when the subjectwas still small, it did not make the subject think negatively about himself and otherpeople. The subject is more grateful for what he has experienced when he was a child,because the subject is more able to take lessons from the experience. Whereas in subjectII even though the subject said that he began to accept himself, subject II sometimes stillcould not accept the conditions he had, blamed himself and the immediate environmentfor the incident and still closed himself in conducting social interactions.